2021
DOI: 10.1158/1538-7445.am2021-1780
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1780: Associations between gut microbiota and PD-L1 immunotherapy/JAK1/2 inhibition in mouse Pten-deficient prostate cancer

Abstract: The gut microbiome is now known to influence host immune function, malignancies, and response to therapy. We previously showed that sequencing PD-L1/JAK1/2 blockade prior to androgen deprivation therapy (ADT) could promote immune activity to potentiate antitumor responses in mouse Pten-deficient prostate cancer. Here, we investigate the associations between the treatment pairings of PD-L1 antibody (aPD-L1, clone D265A, mouse/IgG1 kappa) blockade and the JAK1/2 inhibitor AZD1480 with ADT in mouse Pten-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…50 The interplay between the gut microbiota and the host with cancer burden is complex, and studies have found that glyoxylate and dicarboxylate metabolism, and the citrate cycle (TCA) also have major regulatory roles in prostate cancer mice. 51 Our previous study found that torularhodin inhibits the growth of prostate cancer in mice, 52 which may also be related to the gut microbiome. Therefore, the results from the gut microbiome and metabolome also indicate that torularhodin has a modulating effect on host health.…”
Section: Papermentioning
confidence: 98%
“…50 The interplay between the gut microbiota and the host with cancer burden is complex, and studies have found that glyoxylate and dicarboxylate metabolism, and the citrate cycle (TCA) also have major regulatory roles in prostate cancer mice. 51 Our previous study found that torularhodin inhibits the growth of prostate cancer in mice, 52 which may also be related to the gut microbiome. Therefore, the results from the gut microbiome and metabolome also indicate that torularhodin has a modulating effect on host health.…”
Section: Papermentioning
confidence: 98%